Türkıyeʼs experıence ın organızıng academıc mobılıty (case of the MEB system) - Güler, Cennet (The Lingua Spectrum, 2026)
This study aims to examine the process of assigning teachers and pedagogical personnel abroad by the Ministry of National Education (MoNE) within the scope of educational diplomacy, which is a vital component of the Republic of Türkiyeʼs “soft power” strategy. As in many other countries, high-quality instruction in the Turkish language and culture is primarily facilitated by personnel assigned to Turkology departments or educational institutions where Turkish is taught, particularly in Uzbekistan. Concurrently, inter-state relations are strengthened through various projects implemented based on the “Turkish language bridge”. This article first elucidates the historical background, rationales, and legal foundations of the process; subsequently, it provides a detailed analysis of the mechanism for assigning “lecturers/pedagogical personnel”, candidate selection criteria, examination systems, and their adaptation processes. As a result of the study, detailed information on all these processes is presented, and the finding that a total of 22 Turkish language lecturers are actively serving across Uzbekistan, primarily in the capital, Tashkent, and various other provinces, is shared. The steadily increasing interest in the Turkish language in Uzbekistan suggests that the number of qualified Turkish language instructors should also be increased. Based on the outcomes of this study, the following conclusions and recommendations can be drawn: the need for Turkish language instructors in educational institutions where Turkish is taught, particularly in Uzbekistan, can be addressed in coordination with the Ministry of National Education (MoNE) of the Republic of Türkiye.